PENGARUH MODEL TALKING STICK DALAM PEMBELAJARAN IPS TERHADAP HASIL BELAJAR SISWA KELAS IV SDN 26 PONTIANAK - Hanmurapi, Hanmurapi; Marli, Suhardi; Syamsiati, Syamsiati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research was to know the impact of Talking Stick Model to the social learning outcomes in Elementary School Number twentysix, Pontianak . The experimental reseach method was used in this research. The form of the experimental reseach used was quasi exsperimental design.population in this reseach is all student fourth which consisted of 41. Sampel in this reseach were student fourth grade which consisted of 20. Instrumen gatherer data of student learning the test result obtained from pre-test and post-test. The result of data analysis showed that mean score of student post-test was 74,30. Base on t-twst analysis thitung of (11,04) and ttabel (1,6704). Which mean, thitung (11,04) > ttabel (1,6704), thus then Ha accepted. Then result of effect size was 0,77 which mean medium criteria. So, it can be concluded there was a significant effect of using Talking Stick model to the student learning outcomes on fouth grade Elementary School. Keywords: Study Result, effect, Talking Stick and Social Science